Mathematical modelling of heating and evaporation of a spheroidal droplet. (May 2017) - Zubkov, V.S.; Cossali, G.E.; Tonini, S.; Rybdylova, O.; Crua, C.; Heikal, M.; Sazhin, S.S.
Highlights: A new mathematical model for heating and evaporation of a spheroidal droplet. The influence of droplet non-sphericity on heating and evaporation is studied. Droplet eccentricity tends towards 1 at the end of the evaporation process. Abstract: Most of the currently used models for droplet heating and evaporation are based on the assumption that droplets are perfect spheres. At the same time the shapes of many observed droplets in engineering applications are far from spherical. We have studied the influence of droplet non-sphericity on their heating and evaporation, approximating droplet shapes as prolate and oblate spheroids. The previously developed exact solutions to the heat and mass transfer equations for the gas phase surrounding a spheroidal droplet have been used as boundary conditions for the solutions to these equations in the liquid phase. The temperature gradients inside and at the surface of the droplets, and the changes in their shape during the heating and evaporation process have been taken into account. The effects of surface tension and droplet motion on droplet heating and evaporation are ignored. The results are applied to the analysis of heating and evaporation of an n-dodecane fuel droplet in Diesel engine-like conditions. The effect of droplet non-sphericity is shown to be relatively small for the evaporation time of these droplets with initial eccentricities 2 / 3 ⩽ ε ⩽ 1.5 .